PELIBATAN MAHKAMAH KONSTITUSI DALAM PERUBAHAN (ULANG) UUD 1945 YANG PARTISIPATIF MELALUI KOMISI KONSTITUSI - Huda, Ni’matul (Faculty of Law, Universitas Sebelas Maret, 2013)
Abstractcurrently reappears demands change as a result of the 1945 constitution as a evaluation 10 years after the 1945 constitution implementation after change. In this period there have been several issues submitted to the constitutional court about the testing of individual candidates in the presidential election, additional authority in perppu, constitutional complaint and the constitutional question by the court, the role of legislation optimalization dpd. This paper initiated a change the 1945 constitution more participatory through the constitutional commission more independent than the previous constitutional commission, with a mandate to prepare draft changes the 1945 constitution. Learning from the experience of various countries are also undergoing transition to democracy and constitutional reform, we should initiate to engage the court in a change in 1945 constitution.Keywords: constitutional court, participatory, constitutional commission.AbstrakSaat ini muncul kembali tuntutan perubahan (ulang) terhadap UUD 1945 sebagai hasil evaluasi 10 tahun lebih implementasi UUD 1945 pasca perubahan. Dalam kurun waktu tersebut sudah ada beberapa persoalan yang diajukan ke Mahkamah Konstitusi pengujian tentang calon perseorangan dalam pemilihan presiden, tambahan kewenangan Perppu, constitutional complaint dan constitutional question oleh MK, optimlisasi peran legislasi DPD, dan lain-lain. Tulisan ini menggagas perubahan (ulang) UUD 1945 yang lebih partisipatoris melalui Komisi Konstitusi yang lebih independen dibandingkan Komisi Konstitusi yang sebelumnya, dengan mandat menyiapkan draft perubahan (ulang) UUD 1945. Belajar dari pengalaman berbagai Negara yang juga mengalami transisi demokrasi dan reformasi konstitusi, ada baiknya kita menggagas untuk melibatkan MK dalam perubahan (ulang) UUD 1945.Kata Kunci: Mahkamah Konstitusi, Partisipatif, Komisi Konstitusi